2017
DOI: 10.1371/journal.pone.0186540
|View full text |Cite
|
Sign up to set email alerts
|

Continuous high and low temperature induced a decrease of photosynthetic activity and changes in the diurnal fluctuations of organic acids in Opuntia streptacantha

Abstract: Opuntia plants grow naturally in areas where temperatures are extreme and highly variable in the day during the entire year. These plants survive through different adaptations to respond to adverse environmental conditions. Despite this capability, it is unknown how CAM photosynthetic activity and growth in Opuntia plantlets is affected by constant heat or cold. Therefore, the main objective of this research was to evaluate the short-term effect of high (40°C) and low (4°C) continuous temperatures on the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…It was reported [34] that continuous high (40˚C) and low (4˚C) temperatures caused severe stress to young cactus pear cladodes, but in this case, the cactus pear plants grew in an orchard, and are subjected to ordinary day-night and seasonal weather which allow for acclimation and temperature adaption to occur [35]. In fact, it was found that in CAM plants, the optimal CO 2 fixation rates adapt to current growth temperatures.…”
Section: Does the Environmental Temperature Before Harvest Influence mentioning
confidence: 99%
“…It was reported [34] that continuous high (40˚C) and low (4˚C) temperatures caused severe stress to young cactus pear cladodes, but in this case, the cactus pear plants grew in an orchard, and are subjected to ordinary day-night and seasonal weather which allow for acclimation and temperature adaption to occur [35]. In fact, it was found that in CAM plants, the optimal CO 2 fixation rates adapt to current growth temperatures.…”
Section: Does the Environmental Temperature Before Harvest Influence mentioning
confidence: 99%
“…sinensis is highly significant [ 17 ]. A moderately low temperature aids in the accumulation of organic acids [ 18 ], and longer periods of sunshine did not increase the volatile oil composition [ 19 ]. This may be related to the fact that A .…”
Section: Discussionmentioning
confidence: 99%
“…sinensi s is 6.5–8. Investigation found that the soil in the Gansu production area was alkaline; thus, the content of the index components negatively correlated with the soil pH [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriate soil pH of A. sinensis is 6.5-8. Investigation found that the soil in the Gansu production area was alkaline; thus, the content of the index components negatively correlated with the soil pH [22].…”
Section: Effects Of Topographical and Soil Factorsmentioning
confidence: 98%